Lean Production Implementation on Coffee Beans Business - Nurullaily Kartika; Faiz Prawira Setiawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
The purpose of this study is to analyze the application of Lean Production implementation in Kopi Pak Tani. Waste and a big map of the production process originated from Kopi Pak Tani will be used as data. While the big map of the production process is obtained by observation. The background of this research is to achieve a competitive advantage in the production process in order to compete with other competitors. This research applies the qualitative method which consists of 2 different ways for gaining data. First, data obtained by the interview process will proceed to the data reduction method, data presentation method, and conclusion determination method. Second, data from observation will through VALSAT Process Activity Mapping Analysis. The results of this study will become a guideline to implement a lean business process by looking at the mapping analysis of process activity. Furthermore, from this study, the discovered wastes are in lead time, inventory, defect, and transportation.